3 - Do Votes Count? The Travails of Electoral Politics in Nigeria - Agbaje, Adigun; Adejumobi, Said (Africa Development, 2006)
This paper examines contemporary dimensions of electoral politics in Nigeria against a backdrop of historical experiences. It details issues, events and developments before, during and after elections. Its central argument is that Nigeria has suffered from both institutional (organizations + values /rules/norms) and experiential deficits in regard of required ramparts for electoral politics conducive to democratic renewal and consolidation. Organisations have been bereft of values required for turning them into effective institutions while dominant values have been toxic to democratic politicking. While years of dictatorship under colonial, military and civil rule partly account for the parlous state of electoral politics in Nigeria, the nature of political leadership, its shortsightedness as well as its lack of commitment to and experience in the democratic management of diversity in the context of restrained governance, have devalued politics and elections in Nigeria, reducing the latter literally to an instrument of warfare by other means. Electoral merchants or better still political barons have hijacked the electoral process marginalizing the people, discounte- nancing their voices and choices and steadily sliding the fourth republic on the path of systemic collapse. Engendering a functional and transparent electoral system will require revaluing institutional capacity and political ethos by the political elites in Nigeria.